Review of Three Gurdjieff-Related Books. (1st August 2016) - Azize, Joseph
Abstract : Three recent Gurdjieff-related volumes are reviewed: Women of the Rope comprising diary notes chiefly by Solano and Hulme; The Reality of Being by Jeanne de Salzmann (generally regarded as his leading pupil); and Questions and Answers along the Way which transcribes group meetings with Hugh Ripman. These flesh out Gurdjieff's ideas and methods in important ways. Most significantly, a good deal of light is shed on Gurdjieff's introduction of contemplation-like inner exercises. The most important of these is the daily "meditation" which he called "the Preparation". Also, it is suggested that Gurdjieff's system, originally designed to harmonise "Eastern" and "Western", underwent a process of "Easternization" after his death in 1949.